Factors Affecting the Drinking Rate of Adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study was conducted to identify the factors affecting the drinking rate of adolescents in one region. This study aimed to investigate whether parental attitudes toward children's drinking and possession of alcohol at home affect adolescent drinking. For data analysis, the odds ratio was obtained through logistic regression analysis. As a result of this study, parents' attitudes toward their children's drinking and whether or not alcohol was kept at home were found to be major influencing factors on the ‘drinking experience rate’, ‘current drinking rate’, and ‘risk drinking rate’ among adolescents. Parents should be educated to firmly oppose the drinking of their children, and awareness should be raised to establish a culture of not keeping alcohol at home.